If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y + -5) = 36 Reorder the terms: (-5 + Y) = 36 Remove parenthesis around (-5 + Y) -5 + Y = 36 Solving -5 + Y = 36 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + Y = 36 + 5 Combine like terms: -5 + 5 = 0 0 + Y = 36 + 5 Y = 36 + 5 Combine like terms: 36 + 5 = 41 Y = 41 Simplifying Y = 41
| 8x-1=5x+10 | | -9x^2=4 | | (7-5i)+(6+9i)= | | 4(a-6)=0 | | -2(3x+3)=24 | | 5r^2+42r+42=-7 | | 124=321+E | | 3z=13-22 | | 6(4x-10)+5-4x=15-6x+4x-10 | | 3x+5-5x=6x+12 | | 2x=9x+27 | | (0.25*4)+(0.1*4+3)=x | | 7(x-5)=-(11-x) | | (6p+1)(p-5)=0 | | -9v=-90 | | 9u=45 | | 5-2x=17+4x | | 5y+2(33y-1)=y-(y+2) | | 3x-4(3x)=9 | | 3x-1=5x+13 | | 710(1-9x)=0 | | 3x-4(-1)=9 | | 750(1-15x)=0 | | 1.5(x-10)=41 | | 0=11x-60 | | 3(d-1+4)=-2d | | 1.5(41-10)=41 | | 50.00+0.50x=300 | | m-.65(e-w)=a | | (x+7)*2-5=39 | | 18=-4x-4 | | V^2-6v-14=0 |